Pengaruh Kompetensi Aparat Desa dan Komitmen Organisasi Terhadap Akuntabilitas Dana Desa: Studi pada Desa Muara Niro Kecamatan VII Koto Kabupaten Tebo - Tarjo Tarjo (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
This research was conducted with the aim of testing the influence of the competency variables of village officials and organizational commitment to the accountability of village funds in Tebo district. The method used in research with survey methods. The sample in this study were 92 respondents taken using simple random sampling technique. Data analysis using multiple linear regression with the help of IBM applications. Version statistics. 20 The results of the research partially prove the influence of the competence of village officials H1 on accountability of village funds, proved to have a significant effect with a significance value of 0.000 <0.05. H2 influence of organizational commitment to the accountability of village funds the significance value of 0.000 <0.05 then H2 is proven to have a significant effect. Simultaneously H3 influence the competence of village officials and organizational commitment together has a significant effect with a value of 0.000 <0.05.